Enzymatic extraction of ficus deltoidea for better enhancement of extracted yield - Hazwani, Sidek Haron (2014)
This thesis reported the enzymatic extraction of Ficus deltoidea (mas cotek) for better enhancement of extracted yield. F. deltoidea from Moraceae family which also known as “mas cotek”, “serapat angin” and “telinga beruk” in Malaysia, “tabat barito” in Indonesia and “ kangkalibang” in Africa. This plant has many used in traditional medication such as to help uterus contraction after deliver, improve blood circulation, reducing cholesterol, treat diabetes and also can use as aphrodisiac. Previous research had shown that there were several active compounds in F.deltoidea which are flavonoids, phenol, tannis, riterpenoids, isovitexin, vitexin, proanthocyanidins, flavan-3-ol monomers and flavones glycosides. Since the uses of active compound of this plant have been known and have the high demand, there are several extraction technique have been research. However, the ideal technique is not reported yet. Hence, this work aims to study the most ideal extraction technique of F.deltoidea. The F. deltoidea ground leaves are added into the water to form suspension. The ground leaves are extracted by using two methods which is hydro distillation which is extraction by using water only and enzyme cellulase extraction which is the extraction wit enzyme assist. For the first enzymatic extraction, the different concentrations of enzyme cellulase but same temperature which is 500C are used to get the optimum concentration. For the second enzymatic extraction used different temperature from the optimum concentration. The suspension is separated to oil-rich and emulsion phase by using centrifuge. The extraction is withdrawn by using micropipette. Then, the extracted active compound is analyzed by using high performance liquid chromatography (HPLC) to identifying and purifying the active compounds of the mixture. The isovitexin is used as the standard which is the active compound that will be detected by HPLC. According to the HPLC analysis, the retention time of isovitexin detected is around 13 min to 14 min for the standard solution. The optimum concentration for enzyme extraction is 1 mg/L. The yield of the enzymatic assist is higher than the control extraction which is without enzyme